1996
DOI: 10.1099/00222615-44-6-482
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of different PCR-based DNA fingerprinting techniques for typing of the Acinetobacter calcoaceticus-A. baumannii complex

Abstract: Different PCR-based DNA fingerprinting techniques were evaluated for typing 26 clinical isolates belonging to the Acinetobacter calcoaceticus-A. baumannii complex. Seven isolates belonged to a previously defined outbreak while 19 isolates were unrelated epidemiologically. The PCR-based DNA fingerprinting techniques used were: (i) repetitive extragenic palindromic (REP) PCR; (ii) enterobacterial repetitive intergenic consensus (ERIC) PCR; (iii) randomly amplified polymorphic DNA with M13 forward primer; (iv) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
1
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 32 publications
0
80
1
5
Order By: Relevance
“…A dendrogram created using the Rep-PCR results demonstrated only one distinct cluster with Ͼ90% similarity (see Fig. S4 in the supplemental material), a cutoff level above which isolates can be considered genetically related (21,46,47). This cluster included eight A. baumannii isolates involved in a prolonged multistate outbreak from 2005 to 2006.…”
Section: Resultsmentioning
confidence: 99%
“…A dendrogram created using the Rep-PCR results demonstrated only one distinct cluster with Ͼ90% similarity (see Fig. S4 in the supplemental material), a cutoff level above which isolates can be considered genetically related (21,46,47). This cluster included eight A. baumannii isolates involved in a prolonged multistate outbreak from 2005 to 2006.…”
Section: Resultsmentioning
confidence: 99%
“…The Mg 2ϩ concentration was 3 mM, and the primers were used at 0.5 M each. The primer pair REP1 (5Ј-IIIGCGCCGICATCAGGC-3Ј) and REP2 (5Ј-ACGTCTTATCAGGCCTAC-3Ј) was used to amplify putative REP-like elements in the genomic bacterial DNA (23). A total of 500 ng of chromosomal DNA was added to the reaction mixture.…”
Section: Selection Of Clinical Isolates and Patientsmentioning
confidence: 99%
“…Contrary to this method, several authors (3,4) have shown that repetitive extragenic palindromic PCR (REP-PCR) is a simple, rapid, and relatively low-cost method, useful in the characterization of nosocomial outbreaks of A. baumannii infections, being comparable to pulsed-field gel electrophoresis in regard to discriminatory power and reproducibility. Moreover, REP-PCR has a higher power of discrimination and reproducibility than do other PCR-based fingerprinting systems (3,11,17,23,25).…”
mentioning
confidence: 99%